The Debate of Menaḥem and Dunash and a Frame-work for Non-Triliteral Hebrew Verbal Morphology - Dachman, Joshua (Journal of Semitic studies, 2022)
This study presents a new suggestion as to the fundamental disagreement between the morphological theories of Menaḥem b. Saruq and Dunash b. Labraṭ, two tenth-century Hebraists with non-triliteral perspectives of the Hebrew root. A framework detailing the possible analyses of Hebrew verbal morphology without a priori assuming the triliteral perspective is first developed. It is noted that the multiplicity of possible analyses in this framework parallels the ‘Segmentation Problem’ of Romance languages due to thematic vowels. Based on analysis of their treatises it is then argued that Menaḥem generally follows one identified method of analysis, and Dunash another. Finally it is suggested that these different methods of analysis are rooted in two different models of morphology, with Menaḥem holding a morpheme-based model and Dunash holding a word-based model. An English translation of a lengthy relevant section of the introduction to Menaḥem’s treatise is given as an appendix.